2020
DOI: 10.1016/j.chaos.2020.109988
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the dynamics of COVID-19 pandemic in India under lockdown

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 10 publications
1
59
0
1
Order By: Relevance
“…Researchers are involved to create theories and forecasting models [ 99 , 100 ]. It is certain that during the first phase of lockdown COVID-19 infected cases were under controlled [ 101 ]. Because of the population and population density lockdown was needed [ 102 ].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers are involved to create theories and forecasting models [ 99 , 100 ]. It is certain that during the first phase of lockdown COVID-19 infected cases were under controlled [ 101 ]. Because of the population and population density lockdown was needed [ 102 ].…”
Section: Discussionmentioning
confidence: 99%
“…Then, to counter the fast contagion of COVID-19, a 3-week nationwide lockdown was imposed in India on March 24, which was expended till June 30. The lockdown measures mitigate the impact of COVID-19 on Indian health infrastructure and it also helped in curbing the rate of the spread of this infectious disease among people (Pai et al, 2020;Anderson et al, 2020). Because of the prohibition of industrial activities and mass transportation, anthropogenic emissions showed a tremendous reduction.…”
Section: Introductionmentioning
confidence: 99%
“…The model predicts peak of cumulative cases around 43,000 in mid-May. However, 7-21% increase in peak value of cases was predicted for post lockdown period, re ecting relaxation in control strategies [20]. The evolution of COVID-19 in topmost affected states of India was done using SISO model [23].…”
Section: Discussionmentioning
confidence: 99%